Clinical Reasoning Web‐based Prototypic Module for Tutors Teaching 5th Grade Medical Students : A Pilot Randomized Study. (27th March 2015) - Stein, Gerald H.; Tokunaga, Hironobu; Ando, Hirotaka; Obika, Mikako; Miyoshi, Tomoko; Tokuda, Yasuharu; Noguchi, Yoshinori; Kinjo, Mitsuyo; Kohsaka, Shun; Honda, Hitoshi; Kitano, Yuka; Kitazono, Hidetaka; et al.
Abstract : Background: At present clinical reasoning skills are not systematically taught in Japanese medical universities. We developed a prototypic preliminary module for clinical tutors to introduce clinical reasoning to Japanese medical students. We hypothesized that tutored medical students would outperform self‐study students. Method: Using the web‐based Sequential Question and Answer test that rewarded history and differential diagnosis as proxies for clinical reasoning, we compared the pre and posttest scores of 12 randomized fifth grade tutored students at two universities during four tutor‐led 1.5‐hour web‐based seminars using a structured syllabus to 12 randomized self‐study students. Results: The tutored and self‐study groups' pretest scores were statistically similar at about 40 out of 100 weighted correct points. The tutored students' posttest scores were 62 points, significantly greater (p = 0.007) than the pretest mean 42 points, compared to the self‐study students' posttest scores of 52 points, significantly greater (p = 0.012) than pretest mean 40 points. The difference between the two posttest groups was of borderline statistical significance (p = 0.08). Conclusions: We successfully assessed a prototypic module for tutors to introduce clinical reasoning to Japanese medical students. The tutored students achieved higher scores than the self‐study students. Further research is needed to exploit the potential of our modular clinical reasoning system.